Representations of law in popular culture: Knowledge constructions, media deconstructions - Rivalland, Virginia (1996)
This thesis investigates law and analyses its representations in popular culture. Law is a powerful institution within western society with a regulatory role that is supported by a range of complementary discourses that accord with society's dominant cultural values. This thesis proposes that while such institutional hegemony is never stable as there is always an expectation of challenge or resistance, law is currently experiencing a series of challenges on numerous fronts. Legal commentators themselves acknowledge that law now faces a ‘crisis of confidence' that may affect its status and impact on its power to control and regulate. Media are cultural phenomena that can point to changes occurring in society and this thesis, in examining law's representations in popular culture, seeks to determine whether challenges, as oppositional discourses, are present and available to media audiences. Law is generally regarded as 'over-represented’ in popular culture, and television in particular has developed a special relationship with the stories of law based on a shared preference for ideological closure. This thesis uses textual analyses to examine to what extent the challenges to law are allocated textual space within the texts of popular culture as oppositional discourses and alternative versions of reality